The stigma and challenges faced by retired professional male rugby players - Heimler, S.; Cushion, C.; Piggin, J.; Manoli, A. E. (Qualitative Research in Sport, Exercise and Health, 2025)
Mental health challenges faced by retired athletes are not simply about individuals but are grounded in the relational and sociocultural contexts of their sports careers, and are potentially amplified through stigmatisation after retirement. Aligned with a constructionist paradigm, we aimed to explore how career experiences shaped retirement transitions of professional rugby players. Interviews with 20 former elite male rugby union players were analysed using Goffman`s concepts of total institutions and stigma, and Scott`s notion of reinventive institutions. Participants` experiences indicated the development of singular rugby identities, characterised by a focus on playing rugby above everything else, embodying values of sacrificing for the team and limited or no engagement with support before, during, or after retirement. Following retirement, participants often realised how much they were moulded by, and reliant on, rugby`s institutional structures. The loss of these structures tended to increase feelings of being lost, lacking purpose and social isolation. Participants` experiences reflected stigmatisation and social rejection when attempting to engage with the professional rugby world as if they were still active players. Their rugby identities often persisted beyond retirement, making it difficult to engage with support - a challenge compounded by the perception that showing distress would not align with their `strong champion` identities. The analysis suggests that improving support services before and after retirement requires institutional changes that address the moulding of singular athletic identities. These findings can inform debates around duty of care in sport in general, and rugby union specifically.